Analisis Bauran Distribusi Pada PT. Dakota Cabang Indragiri Hulu Provinsi Riau : Studi Kasus Pada Produk MPASI - Muhklas Adi Putra; Said Afriaris (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
Companies need a marketing activity to distribute goods and connect producers to consumers, so that the products produced reach the community, one of which is through the right distribution channels. The research method used is a type of qualitative descriptive analysis research using data collection techniques through interviews, observation and documentation. The results of this study indicate that the distribution mix at PT. DAKOTA Branch of Indragiri Hulu Agen Belilas is seen from the distribution channels used and the distribution channel procedure in distributing complementary food products for Mother's Milk (MPASI) in Indragiri Hulu Regency, Riau Province.